Marcinkiewicz Integral Operators and Commutators on Herz Spaces with Variable Exponents. (14th October 2014) - Wang, Liwei
Abstract : Our aim in this paper is to give the boundedness of the Marcinkiewicz integralμ Ω on Herz spacesK ˙ p ( · ) α ( · ), q ( R n ) andK p ( · ) α ( · ), q ( R n ), where the two main indices are variable. Meanwhile, we consider the boundedness of the higher order commutatorμ Ω, b m generated byμ Ω and a functionb in BMO( R n ) on these spaces.